Competitiveness of Entrepreneurs and Salaried Workers - Balafoutas, Loukas; Batsaikhan, Mongoljin; Sutter, Matthias (Management Science, 2024)
We measure the willingness to compete of entrepreneurs and salaried workers in an experiment. Participants can choose between a piece rate and a tournament scheme in either private or public. We find that in the private condition, entrepreneurs are less competitive than salaried workers, but in the public condition, this ordering is reversed. Survey data suggest that perceived norms of appropriate behavior, along with beliefs about the instrumental value of competitiveness for professional success, can explain why entrepreneurs are more competitive when decisions are publicly observable. We also find that the latter condition improves the quality of experimental decisions. This paper was accepted by Yan Chen, behavioral economics and decision analysis. Funding: Financial support from the Deutsche Forschungsgemeinschaft (German Research Foundation) under Germany´s Excellence Strategy [Grant EXC 2126/1–390838866], the University of Cologne through the Hans Kelsen Prize and the Austrian Science Fund through the Special Research Area [Grant SFB F63] is gratefully acknowledged. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4838 .